2010
DOI: 10.1002/pssc.200983587
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN HFETs on Fe‐doped GaN substrates

Abstract: AlGaN/GaN HFETs with different undoped GaN thicknesses were grown on Fe‐doped freestanding GaN substrates by conventional MOVPE. To realize a high drain current, thick undoped GaN is found to be necessary. SIMS measurement shows that Fe is redistributed into the epilayer, by which the scattering center is generated at the channel when the thickness of the undoped GaN is insufficient. We also observed a similar Fe profile in the GaN/sapphire template placed on the side of the Fe‐doped GaN substrate during growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…19 However, during the growth of HEMT structures, Fe from the GaN:Fe substrates can incorporate into the GaN epilayer making the sheet resistance worse and, thus, affecting device operation. 20 On the other hand, carbon can be a promising alternative dopant for fabrication of SI bulk GaN substrates by the HVPE method, following an example of successful use of C in metal-organic vapor phase epitaxy (MOVPE) growth of SI GaN layers for HEMT structures. 21 Previously, it was found that doping by C during the HVPE growth of GaN results in increase of YL around 2.2 eV.…”
Section: à3mentioning
confidence: 99%
“…19 However, during the growth of HEMT structures, Fe from the GaN:Fe substrates can incorporate into the GaN epilayer making the sheet resistance worse and, thus, affecting device operation. 20 On the other hand, carbon can be a promising alternative dopant for fabrication of SI bulk GaN substrates by the HVPE method, following an example of successful use of C in metal-organic vapor phase epitaxy (MOVPE) growth of SI GaN layers for HEMT structures. 21 Previously, it was found that doping by C during the HVPE growth of GaN results in increase of YL around 2.2 eV.…”
Section: à3mentioning
confidence: 99%
“…HEMT on the Fe-doped GaN substrate was demonstrated by Oshimura et al [8]. In the present study, in the HEMT structure fabricated on the Fe-doped GaN substrate, it was determined that I DS of HEMT on the Fe-doped GaN substrate deteriorates when the channel layer thickness is insufficient.…”
mentioning
confidence: 51%
“…The local variation in carrier concentration around the Fe 2 O 3 particles can be originated either from the solid phase diffusion of Fe atoms into GaN during the annealing process after the cocatalyst deposition, or by the formation of a junction between GaN and Fe 2 O 3 . Although it has been shown that Fe atoms can diffuse into GaN as far as 1 μm if it is annealed at 1,050 °C 35 , the low temperature of our annealing process (500 °C) and the exponential dependence of the diffusion coefficient on temperature suggest that the doping effect is not considerable. Besides, Fe atoms in GaN act as acceptor-like point defects 36 , decreasing the n-type carrier concentration of GaN.…”
Section: Resultsmentioning
confidence: 83%